Pemilihan Karier Akuntan Publik: Determinasi Faktor Internal Dan Eksternal Saat New Normal Pada Lulusan S1 Akuntansi Di Indonesia - Juan Carlos Pangestu; Phebyana Margaretha; Tristian Valentino (Owner : Riset dan Jurnal Akuntansi, 2022)
Indonesia Business Sector is still experiencing a shortage in terms of the number of public accountants. The need for this number of public accounting professions is an opportunity for S1 graduates to pursue career become a public accountant The need for this number of public accounting professions is certainly an opportunity for undergraduate accounting graduates to work as professional public accountants. However, to become a profession, you must pass the basic level exam, professional level exam and audit experience assessment The research aims to determine the influencing factors S1 graduates in Indonesia to be a public accountant. This research method is quantitative by using multiple regression analysis.. The results showed that the variables of Public Accountant Perception, Knowledge of Accounting Science, Market Considerations showed a significant impact on Career Interest of undergraduate accounting graduates to pursue carrer become a public accountant while Financial Rewards (Financial Rewards) have no significant effect . Suggestions for this research is to add respondents who fill out research questionnaires or undergraduate accounting graduates to be used as research samples. The distribution of questionnaires was also carried out not only in Java, but also on the island of Sumatra and also the island of Kalimantan which will become the capital of the archipelago in the future, so this research can analyze whether interest in a career as a professional Public Accountant is also owned by prospective accounting graduates outside Java.